Preparation process of PET (Polyethylene Terephthalate) heat-insulating master batch
By using the design of ternary heterogeneous filler and gradient hole hollow glass microbeads in the PET thermal insulation masterbatch preparation process, the problems of uneven dispersion and poor compatibility of fillers are solved, and high thermal insulation performance and high mechanical properties are achieved.
Patent Information
- Application Number
- CN202510378740.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing PET thermal insulation masterbatch preparation process has problems such as uneven dispersion, poor compatibility and low processing efficiency, which affects the thermal insulation performance and application effect.
By optimizing raw material selection, filler modification and processing technology, the cross-scale design of ternary heterogeneous fillers (boron nitride/zinc oxide/graphene) and gradient pore hollow glass microbeads is adopted, and the thermal conductivity of the filler is used to direct the lateral diffusion of heat, reduce the interface thermal resistance, and improve the phonon scattering efficiency.
The thermal insulation performance and production efficiency of PET thermal insulation masterbatches are significantly improved, and the high thermal insulation performance and high mechanical properties are achieved. The thermal conductivity is close to that of aerogel but has high strength.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PET masterbatches, and in particular to a preparation process of PET thermal insulation masterbatches. Background Art
[0002] As a lightweight, high-strength, and easy-to-process thermoplastic polymer material, PET is widely used in packaging, electronic devices, building insulation, and other fields. However, the traditional PET material itself has a high thermal conductivity and is difficult to meet the needs of high thermal insulation scenarios. In the prior art, the preparation process of PET thermal insulation masterbatch has problems such as uneven filler dispersion, poor compatibility, and low processing efficiency, which affect the thermal insulation performance and application effect. To solve these problems, the prior art improves the thermal insulation performance of PET materials by adding thermal insulation masterbatch. For example, as disclosed in Chinese patent CN201711219035.4, the present invention discloses an ultra-high weather-resistant, low-transmittance, high-insulation inorganic functional masterbatch, which is prepared by granulating PET plastic slices and nanopowders of ultra-high weather-resistant, low-transmittance inorganic thermal insulation pigments with an average particle size of ≤40nm through a plastic granulator, and the addition amount of the ultra-high weather-resistant, low-transmittance inorganic thermal insulation pigment is 1-15wt% of the inorganic functional masterbatch. The inorganic functional masterbatch can be widely used in the fields of thermal insulation window film, textile, plastic sheet, plastic greenhouse and glass laminated film. However, while improving the thermal insulation performance, the method lacks multi-component collaborative design, and the thermal insulation efficiency and mechanical properties are limited. On the other hand, Chinese patent CN201610948551.X discloses a carbon fiber reinforced PET composition and a preparation method thereof, which is prepared by mixing and extruding granulation of 30-60 parts of PET, 5-10 parts of PTT, 25-45 parts of carbon fiber, 5-15 parts of hollow glass microspheres, 0-5 parts of toughening agent, 5-10 parts of nucleating agent and 5-10 parts of surface improver. Through the mutual cooperation between hollow glass microspheres and surface improvers, the floating fiber phenomenon on the surface of the PET composition after injection molding is improved together, and the compressive performance of the glass fiber reinforced PET composition is improved. Although this method improves the mechanical properties of the PET material to a certain extent, it is limited to the improvement of thermal insulation performance.
[0003] In view of this, research and improvement are conducted on the existing technology and its deficiencies, and a PET thermal insulation masterbatch preparation process is provided. By optimizing raw material selection, filler modification and processing technology, the thermal insulation performance and production efficiency of PET thermal insulation masterbatch are improved to meet the thermal insulation needs of construction, automobile and other fields. Summary of the invention
[0004] In order to solve the problems mentioned in the above background technology, the present invention provides a process for preparing PET thermal insulation masterbatch.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A PET thermal insulation masterbatch preparation process comprises the following steps: Step A, mixing PET resin, thermal insulation filler, silane coupling agent, dispersant, antioxidant and lubricant in a high-speed mixer for 10 to 15 minutes, integrating an ultrasonic generator on the side wall of the mixing chamber of the mixer to destroy filler agglomerates in real time to obtain a mixed material; the thermal insulation filler is composed of hollow glass microspheres and heterogeneous fillers, and the heterogeneous filler includes a ternary heterostructure of boron nitride (BN), zinc oxide (ZnO) and graphene, wherein the weight ratio of BN, ZnO and graphene is 5:3:2, and chemically bonded by a titanate coupling agent, the alkoxy group of the acid ester reacts with the surface hydroxyl group of BN / ZnO to form a Ti-OB / Ti-O-Zn bond, and the graphene is combined with the benzene ring of the titanate through a π-π bond to realize a three-dimensional heterogeneous interface, thereby improving the dispersibility of the filler in the PET matrix, reducing the interface thermal resistance, and improving the phonon scattering efficiency; Step B, adding the mixed material into a twin-screw extruder for melt blending and granulation, wherein the twin-screw extruder has a screw length-to-diameter ratio of 40-45:1, a body temperature of 270-300° C., and a screw speed of 200-300 r / min; The screw speed of the twin-screw extruder decreases gradually from the feeding section to the die head, and the front box temperature is 265-275°C.
[0006] Preferably, the method for preparing the heterogeneous filler comprises: Boron nitride powder (particle size 50-70nm) and nano zinc oxide (particle size 30-50nm) were mixed in a weight ratio of 5:3, titanate coupling agent (KR-TTS, added in an amount of 0.8% of the total weight) was added, and the mixture was ball-milled in a vacuum ball mill at a speed of 150r / min for 4 hours; Graphene sheets (thickness 50-400 nm, sheet diameter 10-20 μm) were added, ball milled for 2 hours, and the vacuum degree was controlled to be ≤20 Pa and the temperature to be 80±5° C. to obtain the heterogeneous filler.
[0007] Furthermore, the silane coupling agent is 3-aminopropyltriethoxysilane (APTES), and the dispersant is a compound system of APTES and polyethylene glycol-b-polyacrylic acid (PEG-b-PAA, molecular weight 5000), and the compound weight ratio is 1:0.3; the mixing temperature is 80±5°C, and the shear rate is 200-400s⁻¹.
[0008] As a preferred solution of the present invention, the antioxidant is triphenyl phosphite, the lubricant is pentaerythritol ester, and copper nanowires (diameter 30-80nm, aspect ratio ≥100) are added as a synergistic catalyst; the copper nanowires are added in an amount of 0.1% to 0.5% by weight of the antioxidant, are pre-dispersed in pentaerythritol ester, and are added to the system after ultrasonic treatment (40kHz, 1h), so that the antioxidant reaction of the Cu⁺-catalyzed antioxidant is reduced, thereby reducing the thermal oxidation degradation rate of PET.
[0009] Preferably, the hollow glass microspheres have a gradient pore structure, including: an outer layer pore size of 20-30 μm, accounting for 40% to 50%; an intermediate layer pore size of 10-20 μm, accounting for 30% to 40%; an inner layer pore size of 1-5 μm, accounting for 10% to 20%; the gradient pores reduce the effective thermal conductivity by multiple scattering phonons and blocking thermal convection, and the preparation method thereof includes: Borosilicate glass powder was mixed with deionized water at a ratio of 1:3, 2 wt% dispersant was added, and ball milling was performed for 4 h to form a uniform slurry; Glass precursor microbeads with a particle size of 50-100 μm were obtained by spray drying granulation; The centrifugal coating-template method was used to construct a pore size gradient in three layers, and then hollow glass microspheres with a gradient pore structure were formed through staged high-temperature sintering.
[0010] Preferably, the silane coupling agent is any one of KH570, KH550, and KH-792, the dispersant is any one of polyethylene wax, calcium stearate, PEG-b-PAA, and maleic anhydride grafted PE, the antioxidant is any one of triphenyl phosphite, Ultranox626, Irganox1076, and Irgafos168, or a combination of two thereof, and the lubricant is any one of pentaerythritol ester, zinc stearate, and silicone masterbatch.
[0011] Preferably, the specific surface area of the heterogeneous filler is 15-20m² / g, the spacing between graphene sheets is 0.8-1.2nm, the boron nitride sheets and graphene are arranged in vertical intercalation, and zinc oxide nanoparticles are embedded in the interlayer gaps. The vertical intercalation structure of boron nitride inhibits matrix deformation and improves the bending modulus. Even if part of the heat enters the material through conduction, the directional heat conduction of boron nitride / graphene can quickly conduct it to the heat dissipation area to avoid internal heat accumulation.
[0012] Preferably, the surface of the copper nanowires is modified with dodecyl mercaptan (C 12 H 25 SH), the modification layer thickness is 2-5nm, through the thiol-copper coordination bond, the thiol modification layer reduces the interface compatibility between copper nanowires and PET, forms a nanoscale air gap (≈1nm), and increases the interface thermal resistance.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The PET thermal insulation masterbatch of the present invention uses the cross-scale design of the chemical bonding of the ternary heterogeneous filler (boron nitride / zinc oxide / graphene) and the gradient hole hollow glass microspheres to directional guide the heat to diffuse horizontally rather than penetrate vertically by using the thermal conductivity of the filler. Graphene can improve the tensile strength of the PET thermal insulation masterbatch, and the vertical intercalation structure of boron nitride inhibits the deformation of the matrix and improves the bending modulus. Even if part of the heat enters the material through conduction, the directional heat conduction of boron nitride / graphene can quickly conduct it to the heat dissipation area to avoid internal heat accumulation. The thermal conductivity of the gradient hole hollow glass microspheres is relatively low, which can make up for the high thermal conductivity of boron nitride / graphene. Through microstructure design and interface engineering, the high thermal conductivity of the filler is converted into a thermal management advantage rather than simply conducting heat. The ternary filler system has enhanced in-plane thermal conductivity, which is beneficial for lateral heat dissipation, while significantly reducing normal thermal conductivity, thereby blocking longitudinal heat transfer. Its thermal conductivity is closer to that of aerogels than that of traditional PET composite materials, but it also has high mechanical strength. The boron nitride flakes are arranged vertically (spacing 0.8-1.2nm) to form a "rebar-like skeleton", and the graphene flakes are horizontally oriented to absorb crack energy, achieving a breakthrough in the mechanical properties of thermal insulation materials. DETAILED DESCRIPTION
[0014] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market, and some of the raw materials can be obtained by oneself.
[0016] Preparation Example 1 Hollow glass microspheres with gradient pore structure 1. Preparation of Precursor Microbeads Borosilicate glass powder was mixed with deionized water at a ratio of 1:3, 2 wt% dispersant (sodium hexametaphosphate) was added, and the mixture was ball-milled for 4 h to form a uniform slurry.
[0017] Glass precursor microbeads with a particle size of 50-100 μm were obtained by granulation through spray drying (inlet 180°C, outlet 80°C).
[0018] 2. Use centrifugal coating-template method to construct pore size gradient in three layers: Outer layer (20-30μm macropores): PMMA microspheres (25 μm) were mixed with 5 wt % APTES ethanol solution and dispersed by ultrasonication for 30 min.
[0019] The precursor microbeads were placed in a centrifugal coating machine, rotated at 1000 rpm, and sprayed with the PMMA mixture to form an outer coating.
[0020] Dry at 60°C for 2 h to fix the PMMA microspheres on the surface.
[0021] Middle layer (10-20 μm mesopores): Silanized CaCO3 (15 μm) and nano-SiO2 sol were mixed in a ratio of 1:1.
[0022] The mixed slurry was sprayed on the outer PMMA layer at 800 rpm in a centrifuge.
[0023] Dry at 80°C for 3h to solidify the middle layer.
[0024] Inner layer (1-5μm pores): Pure nano-SiO2 sol was diluted to a solid content of 5% and formed into a dense inner layer by centrifugal spraying (500 rpm).
[0025] Heat treatment at 120°C for 1 h completed the initial gelation.
[0026] 3. Staged high temperature sintering The first stage (300℃, 1h): decompose the outer layer of PMMA microspheres (decomposition temperature 250-300℃) to form outer macropores while retaining the middle layer CaCO3 and inner layer SiO2 structure.
[0027] The second stage (800℃, 30min): Decompose the intermediate layer CaCO3 (CaCO3→CaO+CO2↑), release CO2 gas to assist in the formation of mesopores, and preliminarily sinter the glass matrix.
[0028] The third stage (950℃, 10min): The glass matrix is completely melted, the inner layer of nano-SiO2 sol densifies and shrinks to form 1-5μm pores, and the gradient structure is solidified by rapid cooling (10℃ / min).
[0029] 4. Pickling and post-treatment Acid washing: The microbeads were immersed in 1.5 mol / L HCl and ultrasonically treated at 60 °C for 2 h to dissolve residual CaO, and then washed with deionized water until neutral.
[0030] Strengthening treatment: Annealing at 600℃ for 1h to eliminate internal stress and improve mechanical strength.
[0031] Example 1
[0032] A PET thermal insulation masterbatch preparation process comprises the following steps: S1: Preparation of heterogeneous fillers Boron nitride powder (particle size 50-70nm) and nano zinc oxide (particle size 30-50nm) were mixed in a weight ratio of 5:3, titanate coupling agent (KR-TTS, added in an amount of 0.8% of the total weight) was added, and the mixture was ball-milled in a vacuum ball mill at a speed of 150r / min for 4 hours; Graphene sheets (thickness 50-400 nm, sheet diameter 10-20 μm) were added, ball milled for 2 hours, and the vacuum degree was controlled to be ≤20 Pa and the temperature to be 80±5° C. to obtain the ternary heterogeneous structure filler.
[0033] S2: 82.5% PET resin, 15% thermal insulation filler, 1.2% KH570 silane coupling agent, 0.8% polyethylene wax, 0.3% triphenyl phosphite and 0.2% pentaerythritol ester are mixed in a high-speed mixer according to mass percentage for 10 to 15 minutes. An ultrasonic generator (frequency 20-40 kHz) is integrated on the side wall of the mixing chamber of the mixer to destroy filler agglomerates in real time to obtain a mixed material.
[0034] S3: adding the mixed material into a twin-screw extruder for melt blending and granulation, wherein the twin-screw extruder has a screw length-to-diameter ratio of 40-45:1, a body temperature of 270-300° C., and a screw speed of 200-300 r / min; The screw speed of the twin-screw extruder decreases gradually from the feeding section to the die head, and the front box temperature is 265-275°C.
[0035] Example 2
[0036] S1: Preparation of heterogeneous fillers Boron nitride powder (particle size 50-70nm) and nano zinc oxide (particle size 30-50nm) were mixed in a weight ratio of 5:3, titanate coupling agent (KR-TTS, added in an amount of 0.8% of the total weight) was added, and the mixture was ball-milled in a vacuum ball mill at a speed of 150r / min for 4 hours; Graphene sheets (thickness 50-400 nm, sheet diameter 10-20 μm) were added, ball milled for 2 hours, and the vacuum degree was controlled to be ≤20 Pa and the temperature to be 80±5° C. to obtain the ternary heterogeneous structure filler.
[0037] S2: 87.5% PET resin, 10% thermal insulation filler, 0.8% KH550 silane coupling agent, 0.5% calcium stearate, 0.5% triphenyl phosphite and 0.7% zinc stearate are mixed in a high-speed mixer according to mass percentage for 10 to 15 minutes. An ultrasonic generator (frequency 20-40 kHz) is integrated on the side wall of the mixing chamber of the mixer to destroy filler agglomerates in real time to obtain a mixed material.
[0038] S3: adding the mixed material into a twin-screw extruder for melt blending and granulation, wherein the twin-screw extruder has a screw length-to-diameter ratio of 40-45:1, a body temperature of 270-300° C., and a screw speed of 200-300 r / min; The screw speed of the twin-screw extruder decreases gradually from the feeding section to the die head, and the front box temperature is 265-275°C.
[0039] Example 3
[0040] S1: Preparation of heterogeneous fillers Boron nitride powder (particle size 50-70nm) and nano zinc oxide (particle size 30-50nm) were mixed in a weight ratio of 5:3, titanate coupling agent (KR-TTS, added in an amount of 0.8% of the total weight) was added, and the mixture was ball-milled in a vacuum ball mill at a speed of 150r / min for 4 hours; Graphene sheets (thickness 50-400 nm, sheet diameter 10-20 μm) were added, ball milled for 2 hours, and the vacuum degree was controlled to be ≤20 Pa and the temperature to be 80±5° C. to obtain the ternary heterogeneous structure filler.
[0041] S2: 90% PET resin, 5% thermal insulation filler, 0.5% KH570 silane coupling agent, 0.3% PEG-b-PAA polyethylene glycol-b-polyacrylic acid, 0.1% Ultranox626 antioxidant and 1.1% silicone masterbatch are mixed in a high-speed mixer according to mass percentage for 10 to 15 minutes. An ultrasonic generator (frequency 20-40 kHz) is integrated on the side wall of the mixing chamber of the mixer to destroy filler agglomerates in real time to obtain a mixed material.
[0042] S3: adding the mixed material into a twin-screw extruder for melt blending and granulation, wherein the twin-screw extruder has a screw length-to-diameter ratio of 40-45:1, a body temperature of 270-300° C., and a screw speed of 200-300 r / min; The screw speed of the twin-screw extruder decreases gradually from the feeding section to the die head, and the front box temperature is 265-275°C.
[0043] Example 4
[0044] S1: Preparation of heterogeneous fillers Boron nitride powder (particle size 50-70nm) and nano zinc oxide (particle size 30-50nm) were mixed in a weight ratio of 5:3, titanate coupling agent (KR-TTS, added in an amount of 0.8% of the total weight) was added, and the mixture was ball-milled in a vacuum ball mill at a speed of 150r / min for 4 hours; Graphene sheets (thickness 50-400 nm, sheet diameter 10-20 μm) were added, ball milled for 2 hours, and the vacuum degree was controlled to be ≤20 Pa and the temperature to be 80±5° C. to obtain the ternary heterogeneous structure filler.
[0045] S2: 85% PET resin, 12% thermal insulation filler, 1.5% KH-792 silane coupling agent, 0.6% maleic anhydride grafted PE, composite antioxidant (0.3% Irganox1076+0.2% Irgafos168) and 0.4% pentaerythritol ester are mixed in a high-speed mixer according to mass percentage for 10 to 15 minutes. An ultrasonic generator (frequency 20-40kHz) is integrated on the side wall of the mixing chamber of the mixer to destroy filler agglomerates in real time to obtain a mixed material.
[0046] S3: adding the mixed material into a twin-screw extruder for melt blending and granulation, wherein the twin-screw extruder has a screw length-to-diameter ratio of 40-45:1, a body temperature of 270-300° C., and a screw speed of 200-300 r / min; The screw speed of the twin-screw extruder decreases gradually from the feeding section to the die head, and the front box temperature is 265-275°C.
[0047] Example 5
[0048] S1: Preparation of heterogeneous fillers Boron nitride powder (particle size 50-70nm) and nano zinc oxide (particle size 30-50nm) were mixed in a weight ratio of 5:3, titanate coupling agent (KR-TTS, added in an amount of 0.8% of the total weight) was added, and the mixture was ball-milled in a vacuum ball mill at a speed of 150r / min for 4 hours; Graphene sheets (thickness 50-400 nm, sheet diameter 10-20 μm) were added, ball milled for 2 hours, and the vacuum degree was controlled to be ≤20 Pa and the temperature to be 80±5° C. to obtain the ternary heterogeneous structure filler.
[0049] S2: 85% PET resin, 8% ternary heterogeneous structure filler, 4% hollow glass microspheres with gradient pore structure, 1.5% KH-792 silane coupling agent, 0.6% maleic anhydride grafted PE, composite antioxidant (0.3% Irganox1076+0.2% Irgafos168) and 0.4% pentaerythritol ester are mixed in a high-speed mixer according to mass percentage for 10 to 15 minutes. An ultrasonic generator (frequency 20-40kHz) is integrated on the side wall of the mixing chamber of the mixer to destroy filler agglomerates in real time to obtain a mixed material.
[0050] S3: adding the mixed material into a twin-screw extruder for melt blending and granulation, wherein the twin-screw extruder has a screw length-to-diameter ratio of 40-45:1, a body temperature of 270-300° C., and a screw speed of 200-300 r / min; The screw speed of the twin-screw extruder decreases gradually from the feeding section to the die head, and the front box temperature is 265-275°C.
[0051] Comparative Example 1 S1: 85% PET resin, 12% hollow glass microspheres, 1.5% KH-792 silane coupling agent, 0.6% maleic anhydride grafted PE, composite antioxidant (0.3% Irganox1076+0.2% Irgafos168) and 0.4% pentaerythritol ester are mixed in a high-speed mixer according to mass percentage for 10 to 15 minutes. An ultrasonic generator (frequency 20-40kHz) is integrated on the side wall of the mixing chamber of the mixer to destroy filler agglomerates in real time to obtain a mixed material.
[0052] S2: adding the mixed material into a twin-screw extruder for melt blending and granulation, wherein the twin-screw extruder has a screw length-to-diameter ratio of 40-45:1, a body temperature of 270-300° C., and a screw speed of 200-300 r / min; The screw speed of the twin-screw extruder decreases gradually from the feeding section to the die head, and the front box temperature is 265-275°C.
[0053] Compared with Example 1, in Comparative Example 2, the titanate coupling agent was omitted and only physical mixing was performed.
[0054] Comparative Example 3 Compared with Example 1, in step S2 of Comparative Example 3, 75% PET resin, 20% thermal insulation filler, 1.2% KH550 silane coupling agent, 0.8% calcium stearate, 0.3% triphenyl phosphite and 0.2% zinc stearate were mixed in a high-speed mixer according to mass percentage.
[0055] Comparative Example 4 S1: 85% PET resin, 12% solid glass beads, 1.5% KH-792 silane coupling agent, 0.6% maleic anhydride grafted PE, composite antioxidant (0.3% Irganox1076+0.2% Irgafos168) and 0.4% pentaerythritol ester are mixed in a high-speed mixer according to mass percentage for 10 to 15 minutes. An ultrasonic generator (frequency 20-40kHz) is integrated on the side wall of the mixing chamber of the mixer to destroy filler agglomerates in real time to obtain a mixed material.
[0056] S2: adding the mixed material into a twin-screw extruder for melt blending and granulation, wherein the twin-screw extruder has a screw length-to-diameter ratio of 40-45:1, a body temperature of 270-300° C., and a screw speed of 200-300 r / min; The screw speed of the twin-screw extruder decreases gradually from the feeding section to the die head, and the front box temperature is 265-275°C.
[0057] Thermal conductivity test method: The material is made into a disc with a diameter of 10-12mm and a thickness of 1-2mm, and a thin layer of graphite is sprayed on the surface (to enhance the laser absorption rate). The laser pulse irradiates the lower surface of the sample, and the infrared detector records the temperature rise curve of the upper surface. The thermal diffusion coefficient (α) is calculated: α=0.1388*L 2 (L is the thickness, t 1 / 2 is half heating time); Thermal conductivity calculation: λ=α*ρ*Cp (ρ is density, Cp is specific heat capacity, which can be measured by DSC). The test instrument is the laser flash thermal conductivity meter Netzsch LFA467.
[0058] Melt index test method: Add the sample into the barrel of the melt index meter Tinius Olsen MP600, heat to 230°C, apply a standard load of 2.16 kg, make the molten polymer pass through a capillary (diameter 2.095 mm, length 8 mm), measure the mass of polymer extruded within 10 minutes (g), and calculate the melt index (g / 10min).
[0059] Tensile strength test method: Injection molded dumbbell-shaped specimens of Type I (gauge length: 50 mm, 10 mm, 2 mm); test 5 specimens in each group and take the average value. Clamp both ends of the specimen, start the Instron 5967 testing machine, record the load-displacement curve until the specimen breaks, and calculate the tensile strength.
[0060] The thermal insulation effect, melt index and tensile strength of the PET thermal insulation masterbatch prepared in the above Examples 1-4 were tested respectively. The specific test results are shown in Table 1 below.
[0061] Table 1 For performance comparison, the performance of Comparative Examples 1-4 was compared with the aforementioned Example 5, as shown in Table 2 below.
[0062] Table 2 Performance Indicators Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Thermal conductivity (W / m·K) 0.12 0.25 0.30 0.20 0.35 Tensile strength (MPa) 58 38 32 28 45 From the data in the above table, it can be seen that the tensile strength of comparative example 1 is stronger than that of comparative examples 2 and 3. This is because the titanate coupling agent realizes the chemical bonding of boron nitride / zinc oxide / graphene through Ti-O bonds and π bonds, thereby enhancing the interfacial bonding force and avoiding the filler as a stress concentration point leading to a decrease in strength. Comparing Example 5 with Example 1 and Comparative Example 1, the thermal conductivity of Example 5 is lower than that of Example 1 and Comparative Example 1, and its strength is equivalent to that of Example 1. It can be seen that by compounding the gradient pore microbeads with the heterogeneous filler, the thermal conductivity is reduced by 33% compared with that of Example 1 with a single filler system, and the impact strength is increased by 41%, breaking through the bottleneck of "thermal insulation-strength-toughness" that is difficult to take into account in traditional thermal insulation materials.
[0063] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A process for preparing PET thermal insulation masterbatch, characterized in that: The steps include: Step A, mixing PET resin, thermal insulation filler, silane coupling agent, dispersant, antioxidant and lubricant in a high-speed mixer for 10 to 15 minutes, the mixing chamber side wall of the mixer is integrated with an ultrasonic generator to destroy filler agglomerates in real time to obtain a mixed material; the thermal insulation filler is composed of a heterogeneous filler and hollow glass microspheres, the hollow glass microspheres have a gradient pore structure, including: an outer layer pore size of 20-30 μm, accounting for 40% to 50%; an intermediate layer pore size of 10-20 μm, accounting for 30% to 40%; an inner layer pore size of 1-5 μm, accounting for 10% to 20%, the heterogeneous filler includes a ternary heterogeneous structure of boron nitride, zinc oxide and graphene, wherein the weight ratio of boron nitride, zinc oxide and graphene is 5:3:2, and they are chemically bonded by a titanate coupling agent; Step B, adding the mixed material into a twin-screw extruder for melt blending and granulation, wherein the twin-screw extruder has a screw length-to-diameter ratio of 40-45:1, a body temperature of 270-300° C., and a screw speed of 200-300 r / min; The screw speed of the twin-screw extruder decreases gradually from the feeding section to the die head, and the front box temperature is 265-275°C.
2. A process for preparing PET thermal insulation masterbatch according to claim 1, characterized in that: The preparation method of the heterogeneous filler comprises: Boron nitride powder with a particle size of 50-70nm and nano zinc oxide with a particle size of 30-50nm were mixed in a weight ratio of 5:3, titanate coupling agent KR-TTS was added in an amount of 0.8% of the total weight, and the mixture was ball-milled in a vacuum ball mill at a speed of 150r / min for 4 hours; (2) Add graphene sheets with a thickness of 50-400 nm and a sheet diameter of 10-20 μm, ball mill for 2 hours, control the vacuum degree ≤ 20 Pa, and the temperature 80±5° C. to obtain the heterogeneous filler.
3. A PET thermal insulation masterbatch preparation process according to claim 1, characterized in that: The silane coupling agent is 3-aminopropyltriethoxysilane, and the dispersant is a compound system of APTES and polyethylene glycol-b-polyacrylic acid PEG-b-PAA, with a compound weight ratio of 1:0.3; the mixing temperature is 80±5°C, and the shear rate is .
4. A process for preparing PET thermal insulation masterbatch according to claim 1, characterized in that: The antioxidant is triphenyl phosphite, the lubricant is pentaerythritol ester, and copper nanowires with a diameter of 30-80 nm and an aspect ratio of ≥100 are added as a synergistic catalyst; the copper nanowires are added in an amount of 0.1% to 0.5% of the weight of the antioxidant, are pre-dispersed in pentaerythritol ester, and are added to the system after ultrasonic treatment.
5. A process for preparing PET thermal insulation masterbatch according to claim 1, characterized in that: The hollow glass microsphere preparation method comprises: Borosilicate glass powder was mixed with deionized water at a ratio of 1:3, 2 wt% dispersant was added, and ball milling was performed for 4 h to form a uniform slurry; Glass precursor microbeads with a particle size of 50-100 μm were obtained by spray drying granulation; The centrifugal coating-template method was used to construct a pore size gradient in three layers, and then hollow glass microspheres with a gradient pore structure were formed through staged high-temperature sintering.
6. A process for preparing PET thermal insulation masterbatch according to claim 1, characterized in that: The silane coupling agent is any one of KH570, KH550, and KH-792; the dispersant is any one of polyethylene wax, calcium stearate, PEG-b-PAA, and maleic anhydride grafted PE; the antioxidant is any one of triphenyl phosphite, Ultranox626, Irganox1076, and Irgafos168, or a combination of two thereof; and the lubricant is any one of pentaerythritol ester, zinc stearate, and silicone masterbatch.
7. A process for preparing PET thermal insulation masterbatch according to claim 1, characterized in that: The specific surface area of the ternary heterogeneous structure filler is 15-20m² / g, the spacing between graphene sheets is 0.8-1.2nm, the boron nitride sheets and graphene are arranged in vertical intercalation, and zinc oxide nanoparticles are embedded in the interlayer gaps.
8. A process for preparing PET thermal insulation masterbatch according to claim 4, characterized in that: The copper nanowire surface is modified with dodecyl mercaptan C 12 H 25 SH, the modification layer thickness is 2-5nm, and it is bound by thiol-copper coordination bonds.
9. A PET thermal insulation masterbatch prepared by the process according to any one of claims 1 to 8, characterized in that The invention comprises: 8wt% of hollow glass microbeads with gradient pore structure, 4wt% of ternary heterogeneous structure filler, 0.01-0.05wt% of copper nanowires, and the balance of PET resin and additives.
Citation Information
Patent Citations
A carbon fiber reinforced PET composition and its preparation method
CN107974053B
Inorganic functional master batch with ultrahigh weather resistance, low light transmittance and high heat insulation
CN109836780A